Empowering Wana Kriya MSMEs Through Utilizing Local Wood Into Decoration and Accessory Products - Ni Putu Emilika Budi LESTARI; I Kadek PRANAJAYA; Putu Yudha Asteria PUTRI; Ni Made Emmi Nutrisia DEWI; Ni Komang PRASIANI; I Gusti Ngurah Agung Kepakisan MANDALA; Ngurah Gede Dwi MAHADIPTA; Ni Kadek Ayu Pradnya PARAMITA; Gede Dharma Arya WICAKSANA; Irfan CAHYONO; Dhanendra WIRATAMA; Ida Bagus Surya WIBAWA (Akuntansi dan Humaniora: Jurnal Pengabdian Masyarakat, 2025)
This community service program aims to empower the Wana Kriya MSME in Pering Village, Gianyar, Bali through the sustainable use of local wood to create economically valuable decorative and accessory products. The activities are carried out through several stages, including socialization, training in creativity and product design innovation, branding training, photography, product identity, and visual content. In addition, training is provided on digital marketing and social media utilization, MSME management, production, and entrepreneurship. The counseling and community empowerment program is carried out with the theme "Building MSMEs Based on Local Resources: Developing a Creative Economy and Sustainability Towards Creative and Competitive Villages." Appropriate technology support is realized through the provision of tools for cutting and finishing funded by a grant from the Directorate of Research, Technology, and Community Service, Directorate General of Research and Development, Ministry of Higher Education, Science, and Technology for Fiscal Year 2025. The application of digital information technology is carried out through the creation of promotional media on Facebook, Instagram, and marketplace integration. The results of the activities show an increase in the ability of partners to produce local wooden decorative and accessory products that are more creative, high-quality, and have a stronger visual identity and digital marketing strategy. This program encourages the development of the creative economy, sustainability, and competitiveness of Pering Village towards a creative village based on local resources.